Emma of 83rd Street - Bellezza, Audrey; Harding, Emily (Gallery Books, 2023)
"In this debut romantic comedy, a modern retelling of Jane Austen's Emma, a beautiful, clever, and rich Upper East Sider with a passion for matchmaking quickly discovers that the best match of all might just be the one she never saw coming"--